Tender - McKeon, Belinda 1979- (Picador, 2016)
Catherine and James are as close as two friends could ever be. They meet in Dublin in the late 1990s, she a college student, he a fledgling artist - both recent arrivals from rural communities, coming of age in a city which is teeming - or so they are told - with new freedoms, new possibilities. Catherine has never met anyone quite like James. Talented, quick-witted, adventurous and charismatic, he helps Catherine to open her eyes, to take on life with more gusto than she has ever before known how to do. But while Catherine's horizons are expanding, James's own life is becoming a prison: as changed as the new Ireland may be, it is still not a place in which he feels able to be himself. Catherine desperately wants to help, but as life begins to take the friends in different directions, she discovers that there is a perilously fine line between helping someone and hurting them further. And when crisis hits, Catherine must face difficult truths not just about her closest bond - but about herself. From the author of the multi-award-winning debut Solace comes another dazzling exploration of the complexities of human relationships, a novel about friendship and youth, about selfhood and sexuality, about the lies we tell ourselves and the lies we are taught to tell. Brave, moving and powerfully told, Tender confirms Belinda McKeon's status as one of the most exciting contemporary voices in Irish fiction. ...